УМЕНЬШЕНИЕ ПОТЕРЬ ЭНЕРГИИ В СИСТЕМАХ ЭЛЕКТРОСНАБЖЕНИЯ ПОДВИЖНОГО СОСТАВА МЕТРОПОЛИТЕНА ПРИ ИСПОЛЬЗОВАНИИ ЭНЕРГОЕМКИХ НАКОПИТЕЛЕЙ ЭЛЕКТРОЭНЕРГИИ - Жемеров, Г.Г.; Ильина, Н.А.; Тугай, Д.В. (Інститут електродинаміки НАН України, Київ, 2014)
It is shown, that the use of energy-intensive energy storage in subway power systems will not only reduce the total amount of electricity consumed from the network, but also will reduce the energy loss during its transportation and consumption. References 5, figures 2, table 1.